Effect of Explant Types and Benzyl Amino Purine Concentrations on the In Vitro Regeneration of Several Local Eggplant Cultivars - Erniwitama Erniwitama; Taryono Taryono; Rudi Hari Murti (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2018)
Eggplant as a vegetable is generally fresh consumed. Besides having a high nutritive value, eggplant contains solasonine and solamargine, which act as an antibacterial that can inhibit cancer cells, gastrictic and respiratory disorders. Eggplant also provides a unique system to study in vitro regeneration since it can be induced from different explants by different growth regulators and morphogenetic pathways. This study aims to observe the effect of explant types and BAP concentrations on the in vitro regeneration of three eggplant cultivars, Rimbang, Tanteloh and Limao. Leaf and hypocotyl explants were cultured on MS semi solid medium supplemented with BAP and IBA in combination. BAP tested at 1, 2 and 3 mgL-1 while IBA tested at 1 mgL-1. Medium containing 1 mgL-1 IBA used for rooting of regenerated shoot. The experiment was arranged in completely randomized design with five replicates. Each replicate consisted of five leaves and hypocotyl explants. Cultures were incubated at 25±10C, 65% humidity, and 16 hours per day photoperiod. Observation was done for 8 weeks of culture. The result indicated that leaf explants showed shoot initiation within 5 – 9 days of cultured, while hypocotyl explants showed the response within 7 – 12 days of cultured. Shoots formation preceded by swollen on the explants surface followed by emerging light green shoot. Leaf explants cultured on medium supplemented with 3 mgL-1 BAP + 1 mgL-1 IBA showed the maximum number of shoots regeneration while hypocotyl explants showed less of shoots in all medium. Similarly, leaf explants cultured on medium supplemented with 3 mgL-1 BAP + 1 mgL-1 IBA showed the maximum number of roots. Among the cultivars, Rimbang showed the best response than other cultivars.